2012
DOI: 10.1177/2158244012451584
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education for Learners With Disabilities in Botswana Primary Schools

Abstract: Based on the findings of a qualitative case study, this article describes the experiences of key stakeholders about the inclusion of learners with disabilities in regular schools in the South Central Region of Botswana. Multiple stakeholders, such as schoolheads, general education teachers, learners with disabilities, and their peers, from six elementary schools participated in this research. The data collection methods included focus group discussions, school and classroom observations, and document analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
3
29
0
Order By: Relevance
“…Furthermore, they expressed concern about not being able to access special educators regularly due to the limited availability of special educators. This finding is consistent with previous studies that found minimal collaboration between special and general educators due to limited availability of the former (Hammond and Ingalls, ; Mukhopadhyay, Nenty and Abosi, ). The authors in these studies attributed this to lack of resources and time constraints.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, they expressed concern about not being able to access special educators regularly due to the limited availability of special educators. This finding is consistent with previous studies that found minimal collaboration between special and general educators due to limited availability of the former (Hammond and Ingalls, ; Mukhopadhyay, Nenty and Abosi, ). The authors in these studies attributed this to lack of resources and time constraints.…”
Section: Discussionsupporting
confidence: 93%
“…A. R. Kuyini, 2013;A. B. Kuyini & Desai, 2008;Mukhopadhyay, Johnson Nenty, & Abosi, 2012;Peters, 2004;SAP, 2011). Finally, the study is also aimed at examining whether teachers' competence to teach children with LDs in the regular classroom differ due to their background variables such as gender, class size, school location, and teaching experience.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, teaching in large class sizes exacerbates the already tense situation and makes it hard for teachers to meet the needs of all learners in the regular classroom (A. A. R. Kuyini, 2013;Mukhopadhyay et al, 2012). Although the United Nations Educational, Scientific and Cultural Organization's (UNESCO, 2006) offers a holistic approach and practical guidelines for teaching large class sizes, the question is how many teachers in developing countries have access to this information.…”
Section: Gender and Class Sizementioning
confidence: 99%
“…Notwithstanding Section 15 of the Constitution of Botswana prohibiting discrimination on the grounds of race, tribe, disability, and so forth and the introduction of reforms (e.g., revision of the National Education Policy and special needs training for teachers) aimed at improving inclusive education, scholars (e.g., Mukhopadhyay, Nenty, & Abosi, ) argue that educators have preferences regarding the type of disabled learner they desire to teach based on the severity of the disability. These barriers indicate that citizens' support and buy‐in for public policies are as equally important as the support received from high‐level stakeholders such as politicians and bureaucrats.…”
Section: Policy and Institutional Challenges And Successesmentioning
confidence: 99%